Validity and Reliability of the Semmes-Weinstein Monofilament Test and the Thumb Localizing Test in Patients With Stroke - Suda, Mabu; Kawakami, Michiyuki; Okuyama, Kohei; Ishii, Ryota; Oshima, Osamu; Hijikata, Nanako; Nakamura, Takuya; Oka, Asako; Kondo, Kunitsugu; Liu, Meigen (Frontiers in Neurology, 2021)
Background: Somatosensory impairment is common in patients who have had a stroke and can affect their motor function and activities of daily living (ADL). Therefore, detecting and treating somatosensory impairments properly is considered to be very important, and various examinations have been developed. However, the reliability and validity of few of them have been verified due to differences in the procedure of each examiner or poor quantification by the examination itself. Objective: We hypothesized that, with fixed procedures two convenient clinical examinations, the Semmes-Weinstein Monofilament Test (SWMT) and the Thumb Localizing Test (TLT), could provide reliable assessments of light touch sensation and proprioception. The purpose of this study was to verify the reliability and validity of these two examinations as indices of somatosensory impairment of the upper extremity (UE) in patients with chronic post-stroke hemiparesis. Methods: Fifty patients with chronic stroke (median time after onset of stroke, 848 [474–1708] days, mean age 57 [standard deviation 14] years) were enrolled at Keio University Hospital from 2017 to 2018. Examiners learned the original method of the SWMT and the TLT rigorously and shared it with each other. The TLT procedure was partially modified by dividing the location of the patient's thumb into four spaces. Two examiners evaluated the SWMT and the TLT for 2 days, and intra-rater and inter-rater reliabilities were calculated using weighted kappa statistics. In addition to this, the evaluator size score of the SWMT was assessed with Bland-Altman analysis to evaluate systematic bias. The Stroke Impairment Assessment Set (SIAS) sensory items were used to assess validity, and Spearman's rank correlation coefficients were calculated. Results: Intra/inter-rater agreements of the SWMT grade score were 0.89 (thumb, 95%CI: 0.83–0.95)/ 0.75 (0.60–0.91) and 0.80 (index finger, 0.67–0.93)/0.79 (0.66–0.92), and of the TLT they were 0.83 (navel level proximal space, 0.71–0.95)/ 0.83 (0.73–0.92), 0.90 (navel level distal space, 0.85–0.96)/ 0.80 (0.69–0.90), 0.80 (shoulder level proximal space, 0.68–0.92)/ 0.77 (0.65–0.89), and 0.87 (shoulder level distal space, 0.80–0.93)/ 0.80 (0.68–0.92) (P < 0.001, each item). All of them showed substantial agreement, but the MDC of the SWMT evaluator size was 1.28 to 1.79 in the inter-rater test and 1.94–2.06 in the intra-rater test. The SWMT grade score showed a strong correlation with the SIAS light touch sensation item (r = 0.65, p < 0.001), as did the TLT with the SIAS position sense item (r = −0.70–0.62, p < 0.001 each space). Conclusions: The reliability and validity of the SWMT and the TLT were verified. These tests can be used as reliable sensory examinations of the UE in patients with chronic stroke, and especially for the SWMT, it is more reliable for screening.